Why Computer Talents Become Computer Hackers. - ZHENGCHUAN XU; QING HU; CHENGHONG ZHANG (Communications of the ACM, 2013)
A cast study on computer hackers in China is presented, which focused on researching how the college-age computer programmers began committing criminal acts online, such as copyright piracy. School computer hacking policies, the intelligence of the case study participants, and the participants' interest in computers from middle school are discussed, as well as computer security, the social and moral aspects of hacking, and routine activity theory (RAT) and social learning theory (SLT).